Comparative analysis of quality attributes of a human albumin preparation with a modified stabilising composition - M. V. Tomilin; T. V. Korotkova; P. A. Loginov (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. The national and international human albumin preparations registered in the Russian Federation mainly differ in their excipient compositions. While all the international preparations of human albumin contain a mixture of sodium caprylate and N-acetyl-DL-tryptophan, the Russian ones contain only sodium caprylate. However, albumin stabilisation with sodium caprylate at high concentrations affects the ligand-binding properties of albumin. For this reason, as well as to achieve storage stability not only at temperatures of 2 °C to 8 °C but also   at room temperature, most international manufacturers have reduced the sodium caprylate content in albumin preparations and added N-acetyl-DL-tryptophan. This demonstrates the relevance of studying the quality of a new Russian human albumin preparation with a modified stabilising composition, including both sodium caprylate and N-acetyl-DL-tryptophan.Aim. The study aimed at comparing several quality attributes of the human albumin preparation with a modified stabilising composition with those of imported human albumin preparations.Materials and methods. The human albumin preparation with a modified stabilising composition was manufactured by fractionation from donor plasma meeting the requirements of monograph FS.3.3.2.0001.19 of the State Pharmacopoeia of the Russian Federation edition XIV. The quality control was in line with the monograph on human albumin (FS.3.3.2.0006.18), and statistical analysis was conducted in Microsoft Excel in accordance with the general chapter on statistical analysis (OFS.1.1.0013.15).Results. The study preparation complied with the requirements specified in monograph FS.3.3.2.0006.18. All the manufactured batches were clear, thermostable, sterile, and non-pyrogenic. The prekallikrein activator levels were low (below 1 IU/mL). The aluminium content varied from 30.36±10.39 µg/L to 50.22±6.94 µg/L. The study preparation contained sodium ions at a concentration from 127.44±10.46 mmol/L to 145.59±7.32 mmol/L and less than 0.01 mmol/g of potassium ions. The osmolarity exceeded 240 mOsm/L. The content of α- and β-globulins  ranged  from  1.79±0.06%  to  2.24±0.20%.  The  study  preparation  had  a  pH  level  of 6.9 to 7.2. The concentrations of polymers and aggregates did not exceed 0.5%.Conclusions. The quality attributes studied suggest that the human albumin preparation with   a modified stabilising composition is comparable to its international counterparts and that it meets Russian and European pharmacopoeial standards.